Kedudukan Hukum Memo Internal dan Perjanjian Bersama Dalam Pemenuhan Hak Upah Lembur Pekerja : Studi Kasus Putusan PHI Makassar Nomor 30/Pdt.Sus-PHI/2025/PN.Mks - Grace Clara Sari Sinaga (PT. Hasba Edukasi Mandiri, 2025)
This study examines the legal position of internal memos and Collective Agreements in fulfilling workers’ rights to overtime pay through a case study of the Industrial Relations Court (PHI) Makassar Decision Number 30/Pdt.Sus-PHI/2025/PN.Mks. The issues are focused on the validity of an internal memo that sets a 40 percent incentive as a substitute for overtime pay and the use of a Collective Agreement which initially only regulated termination of employment (PHK) as the basis for validating the wage system. This research is a normative juridical study with a doctrinal approach, namely by examining laws and regulations. The results show that the internal memo which reduces overtime rates contradicts the imperative norms of wages and therefore can be declared null and void by law, and the Collective Agreement cannot be extended beyond the agreed scope to validate wage arrangements. Recommendations include the cancellation of the internal memo, recalculation and payment of overtime pay differences in accordance with the provisions, as well as strengthening administrative supervision and company wage practices.